Response to “Self-Care Behavior Based on Knowledge of Patients with Hypertension” [Letter] - Acob JRU; Nugroho HSW; Noviadi P (Vascular Health and Risk Management)
Joel Rey Ugsang Acob,1 Heru Santoso Wahito Nugroho,2 Pitri Noviadi3 1Nursing Department, Visayas State University, Baybay City, Philippines; 2Health Department, Poltekkes Kemenkes Surabaya, Surabaya, Indonesia; 3Health Department, Poltekkes Kemenkes Palembang, Palembang, IndonesiaCorrespondence: Heru Santoso Wahito Nugroho; Pitri Noviadi, Email heruswn@poltekkesdepkes-sby.ac.id; tritritriratnaningsih@gmail.com